Evaluasi Modifikasi Metode Analisis Serat Kasar Bahan Pakan di Laboratorium Nutrisi Ternak Politeknik Pertanian Negeri Pangkep: Evaluation of Modified Methods for Analyzing Crude Fiber in Feed at Animal Nutrition Laboratory of Pangkep State Polytechnic of Agriculture - Fitriastuti, Rahma; Udin, Nurbaya; Alwi, Windawati (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Crude fiber in feedstuffs is the most important point in determining nutrient digestibility in livestock. The crude fiber analysis method in feed ingredients that is commonly used as a reference is the Weende Method. This reference method of crude fiber analysis requires quite a lot of reagent solutions. To improve the efficiency of chemical use and waste, it is necessary to modify the analysis method. The use of modified analytical methods needs to be done through validation of the method in the laboratory. Purpose: This study aims to evaluate the modification of the Weende Method to reduce the number of samples and reagents, thereby reducing waste and increasing cost efficiency. Methods: This study analyzed several forage feed ingredients (indigofera flour, elephant grass and rice straw) using the Weende method and its modification conducted for 7 days. The accuracy test was carried out with a complete randomized design with two replications and data analysis with the T test. In addition, the method validation test was continued which included the recovery value and repeatability. Results: The results of the study showed that the modified method for analyzing roughage did not differ significantly from the reference method (Weende Method). The recovery values ranged from 99.60% to 100.58%, and the precision test yielded coefficient of variation (CV) values ranging from 0.38% to 0.74%. The precision values were lower than the CV of the Horwitz analysis, demonstrating that the modified method provided satisfactory repeatability. Conclusion: Finally, the modified method for analyzing roughage, which uses half the amount of reagents and samples, can be effectively utilized as an analysis method in the laboratory (in-house).